2017
DOI: 10.1080/13625187.2017.1334258
|View full text |Cite
|
Sign up to set email alerts
|

Women’s preferences for menstrual bleeding frequency in 12 European countries: the Inconvenience Due to Women’s Monthly Bleeding (ISY) survey

Abstract: The majority of women in the 12 European countries would prefer to reduce the frequency of menstrual periods. Quality of life was the main factor affecting their preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…On average a woman will spend 65 days per year menstruating [5]. In a survey among European countries, 60% of interviewed women would prefer menstruation to be less frequent than once a month, with quality-of-life considerations given as the main reasons [6]. Few options are available to manage menstruation; in high-income countries (HICs), tampons and single-use pads are commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…On average a woman will spend 65 days per year menstruating [5]. In a survey among European countries, 60% of interviewed women would prefer menstruation to be less frequent than once a month, with quality-of-life considerations given as the main reasons [6]. Few options are available to manage menstruation; in high-income countries (HICs), tampons and single-use pads are commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…10,[15][16][17] In a study conducted in eight different countries, only a third of surveyed women reported a negative impact of menstruation in their lives, whereas, in another study in women taking birth control pills, women who lived in predominantly Catholic countries and young women preferred amenorrhea over regular menstrual cycles. 9,18 In relation to the influence of dysmenorrhea on the perception of menstruation, in 2013, Pitangui et al, carried out a study in adolescents in Brazil and found that, out of 218 healthy female adolescents, 73 % referred dysmenorrhea. 4 In the study by Houston et al, 184 adolescents were surveyed, and the rate of dysmenorrhea was 65 %.…”
Section: Discussionmentioning
confidence: 99%
“…10,[15][16][17] En un estudio realizado en ocho países diferentes, se encontró que solo un tercio de las mujeres encuestadas reportaba un impacto negativo de la menstruación en sus vidas, mientras que, en otro estudio realizado en mujeres que tomaban anticonceptivos, las mujeres que vivían en países predominantemente católicos y las mujeres jóvenes preferían presentar amenorrea que ciclos menstruales regulares. 9,18 Con respecto a la influencia de la dismenorrea sobre la percepción de la menstruación, en 2013, Pitangui y cols., realizaron un estudio en adolescentes en Brasil, en el que encontraron que, de 218 adolescentes sanas, el 73 % refería dismenorrea. 4 En el estudio de Houston y colaboradores, se encuestaron 184 adolescentes y se reportó una frecuencia de dismenorrea del 65 %.…”
Section: Discussionunclassified